O graffiti de mundano e a paisagem urbana: um debate social e artístico na circulação do objeto - Neves, Carlos Alexandre Das [UNIFESP] (2016)
This work aims to study the art of graffiti through the analysis of the trajectory of São Paulo graffiti artist Thiago Teixeira Leite Ackel, who signs his works as Mundano. Mundano is an urban artist who distinguished himself in the graffiti scene in the last twenty years, with works made in unusual places, such as signs of political advertisements, recyclers of cars and scrap collected in the dry bed of the reservoir Atibainha. The reason for the choice of this artist for the study is the fact that Mundano can be considered representative of a new generation of graffiti artists, who in addition to concern themselves with its production and political contestation, also end up taking the gallerist function and graffiti art dealer. This way is followed by other artists in this field on the contemporary world. Mundane as well as other artists such as Os Gêmeos, Zezão, Cranio etc., at the same time showing its presence in urban space with works in various locations such as bridges squares and walls, also realizes a production for trade and for exhibition galleries, a fact that reveals a demand for his art. Thus, in order to develop this productive way of study was organized etapadas the research into three parts; the study of the iconography of graffiti, the Mundano path and the reception of their works by the public. By articulating these three points can have a more extada size of the production of this artist process to understand not only the aesthetic references of their productions, but also how Mundano, to transfer his work to various media and institutionalized spaces allowed his art encontronto circulated to a wider audience than that which commonly enjoys his work in urban space. Thus, the artist not only produces graffiti art, but also writes every day a page of the history of São Paulo graffiti. And study their production and reception of his works, it is a scientific repertoire of production so that will be the basis for future studies that aim to account for the complex story of a kind of intense and ephemeral art such as graffiti.